The problem of Taeniasis and Cysticercosis in Irian Jaya, Indonesia (Medical Journal of Indonesia, 2001)
The disease, caused by the adult and larva of Taenia solium, spread to the western part of Irian Jaya crossing the border of Indonesian to Papua New Guinea. Twenty local health centers reported 638 and 945 new cases with epileptic seizures in 1994 and 1995 respectively. Questionnaires were distributed to 31 respondents with results as follows: 83.9% were illiterate, 93.6% farmers and all of them sometimes ate not well-cooked pork; no other meat was consumed. In this area no healthy drinking water was available; also there was no sanitary facilities. Pigs were roaming around the houses, rarely the pigs were put behind fences. After international collaboration with several institutions, e.g with Asahikawa Medical College, Japan, 29 serum samples were examined by immunoblot with positive results for 67% of the cases suffering from epileptic seizures and 65% with subcutaneous nodules. Moving of people to other areas personal and environmental hygiene, the importance of pigs in the daily life of the community were important issues in maintaning the disease being caused by T.Solium in this area. (Med J Indones 2001; 10: 110-4)Keywords: Taenia solium, Irian Jaya, spreading, international collaboration